Modelling and model validation of an electropneumatic brake on subway trains. (February 2016) - Luo, Zhuojun; Wu, Mengling; Zuo, Jianyong; Tian, Chun
In this paper, a model of the electropneumatic brake used on subway trains is developed; it facilitates brake system analysis, fault diagnosis and controller design. This objective is met by decomposing an electropneumatic brake into smaller modules and developing detailed models at three levels. The basic subcomponent models of the electropneumatic brake are built using a lumped parameter method. Then individual models are developed based on the subcomponent models. Finally, a complete model of the electropneumatic brake is developed by assembling all the valve models. Simulation models of these three levels are built using Matlab-Simulink. Important subcomponent models are verified by comparison with experimental results. Furthermore, a test rig is set-up to validate the complete brake model. Experimental and simulated results suggest that the model is able to closely predict the behaviour of the electropneumatic brake: brake filling and releasing time differences between experimental and simulated results are less than 10%; the cause of steady state pressure error of a real electropneumatic brake can be explained using the model; other behaviour of a real electropneumatic brake (sharp pressure jump and drop, pressure oscillation, thermal exchange) can be predicted and better understood using the proposed model.